Optimizing Operational Efficiency and Productivity of The HD785 Heavy Equipment: Reducing Empty Stop Time (EST) and Increasing Speed Through Fleet Matching at PT PPA’S MIP Site, North Pit (March–October 2025) - Fika Kurniawan; Eko Budi Santoso; Fauzi Jatmiko; Naufal Aulia Mustafa; Bagus Budhi Bowo Laksono (Journal of Social Research, 2026)
This study addresses the critical challenge of optimizing heavy equipment productivity in coal mining operations, particularly focusing on reducing Empty Stop Time (EST) and improving haul truck speed to enhance operational efficiency. At PT Putra Perkasa Abadi (PT PPA) Site MIP, baseline data in March 2025 revealed significant inefficiencies, including high EST (3.5 minutes), low average speed (18.7 km/h), and suboptimal Matching Factor (1.25), resulting in reduced productivity and failure to meet production targets. The objective of this research is to improve fleet performance through a structured Quality Control Circle (QCC) approach using the Plan-Do-Check-Action (PDCA) cycle. The research employed a quantitative and applied methodology utilizing real-time data from the Fleet Management System (FMS), combined with root cause analysis and fleet matching calculations. Improvement interventions included operator coaching systems, updated procedures, dynamic fleet matching, haul road maintenance, and infrastructure enhancement. The results demonstrate significant performance improvements: EST decreased to 1.0 minute, average speed increased to 22.6 km/h, and Matching Factor improved to 0.99. Consequently, productivity rose from 91.22 to approximately 113.9 BCM/hour, and production achievement exceeded targets. Financial analysis indicated a substantial revenue gain with a high return on investment. In conclusion, integrated behavioral, technical, and infrastructural interventions effectively enhance mining productivity, providing a scalable model for operational optimization in similar mining environments